2019
DOI: 10.3389/fimmu.2018.03015
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of Human CD11b+ B1 B-Cells by Trypanosoma cruzi-Derived Proteins Is Associated With Protective Immune Response in Human Chagas Disease

Abstract: B-cells mediate humoral adaptive immune response via the production of antibodies and cytokines, and by inducing T-cell activation. These functions can be attributed to distinct B-cell subpopulations. Infection with Trypanosoma cruzi, the causative agent of Chagas disease, induces a polyclonal B-cell activation and lytic antibody production, critical for controlling parasitemia. Individuals within the chronic phase of Chagas disease may remain in an asymptomatic form (indeterminate), or develop severe cardiomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 65 publications
0
16
0
1
Order By: Relevance
“…It has been suggested that the non‐specific polyclonal B‐cell activation contributes to delay the generation of T. cruzi ‐specific B‐cell responses, thus contributing to parasite escape and establishment of chronic infections 133,134 . Polyclonal B‐cell activation is associated with rapid, innate‐like production of IL‐17 and IL‐10 135,136 but the wider relevance is unclear as both protective 136‐138 and deleterious 51,52,135 roles for such innate‐like B‐cell responses have been documented in different models. The infection also causes a transient, yet marked loss of immature B cells in the bone marrow in experimental mouse models, possibly further compromising the response 139 …”
Section: Stage 2: Adaptive Responses Take Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the non‐specific polyclonal B‐cell activation contributes to delay the generation of T. cruzi ‐specific B‐cell responses, thus contributing to parasite escape and establishment of chronic infections 133,134 . Polyclonal B‐cell activation is associated with rapid, innate‐like production of IL‐17 and IL‐10 135,136 but the wider relevance is unclear as both protective 136‐138 and deleterious 51,52,135 roles for such innate‐like B‐cell responses have been documented in different models. The infection also causes a transient, yet marked loss of immature B cells in the bone marrow in experimental mouse models, possibly further compromising the response 139 …”
Section: Stage 2: Adaptive Responses Take Controlmentioning
confidence: 99%
“…B cells also produce IL‐10, 135 and overall IL‐10 production is lower in B1 B‐cell‐deficient mice early during infection 159 . CD11b + B1 B cells from asymptomatic, infected individuals show increased capacity to produce IL‐10 compared to those with cardiac disease symptoms 138 . In addition, recent data show that when compared to non‐infected donors, chronically T. cruzi ‐infected individuals with cardiac manifestations have an increased proportion of immature transitional CD24 high CD38 high and naïve B cells able to produce IL‐10 upon in vitro re‐stimulation 160 .…”
Section: Stage 2: Adaptive Responses Take Controlmentioning
confidence: 99%
“…In humans, circulating regulatory B10 results altered during the chronic stage and is associated with improved cardiac function in the indeterminate stage of Chagas disease ( Passos et al., 2019 ; Girard et al., 2021 ). Also, since we observed a regulatory phenotype on parasite-stimulated B cells we tested for the presence of IL-21, a cytokine related to regulatory B10 cell generation ( Horikawa et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneous immune response has been reported during infection with L. chagasi , where differential effects on B and T cells were noticed in three different experimental inbred mouse strain [ 38 ]. However, in human Chagas disease, B1 B cells play opposite role, where CD11b+ B1 B cells are responsible for protective immune response [ 39 ]. The interaction between L. donovani amastigotes and purified splenic B cell induces IL-10 secretion by MZ B cell and Breg B cells leading to disease exacerbation [ 40 ].…”
Section: Discussionmentioning
confidence: 99%